Bood lactate. Implications for training and sports performance - Jacobs, I. (Sports Medicine, 1986)
The blood lactate response to exercise has interested physiologists for over fifty years, but has more recently become as routine a variable to measure in many exercise laboratories as is heart rate. This rising popularity is probably due to: a) the ease of sampling and improved accuracy afforded by recently developed micro-assay methods and/or automated lactate analysers; and b) the predictive and evaluative power associated with the lactate response to exercise. Several studies suggest that the strong relationship between exercise performance and lactate-related variables can be attributed to a reflection by lactate during exercise of not only the functional capacity of the central circulatory apparati to transport oxygen to exercising muscles, but also the peripheral capacity of the musculature to utilise this oxygen. For example, several studies contrast the relationship between VO2max and endurance running performance with that between a lactate variable and the same running performance. In every study, the lactate variable is more highly correlated with performance. Similarly, prescribing training intensity as a function of the lactate concentration elicited by the training may prove to be a means of obtaining a more homogeneous adaptation to training in a group of athletes or subjects than is obtained by setting intensity as a function of maximal heart rate or % VO2max. A review of the recent literature shows that the lactate response to supramaximal exercise is a sensitive indicator of adaptation to `sprint training` and is correlated with supramaximal exercise performance. This review also describes the possible applications of lactate measurements to enhance the rate of recovery from high intensity exercise. Although the lactate response to exercise is reproducible under standardised conditions it can be influenced by the site of blood sampling, ambient temperature, changes in the bodys`s acid-base balance prior to exercise, prior exercise, dietary manipulations, or pharmacological interpretation.